Analisis Pengendalian Biaya Bahan Baku dengan Menggunakan Metode Economic Order Quantity (EOQ) - Purnamasari, Atika (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To analyze raw material cost control at PT Indo Porcelain using the Economic Order Quantity (EOQ) method. Background Problems: Controlling the most appropriate raw material inventory so that production activities are not disrupted and funds invested in material inventory are not excessive. Novelty: Re-testing the EOQ method in different companies as well as the time of research. Research Methods: Using the EOQ method is used to determine the optimal number of orders and the frequency of ordering raw materials that must be made by a company to minimize inventory and ordering costs. Finding/Results: By implementing the EOQ method, the company is able to control raw material costs effectively. Conclusion: The EOQ method is effective in controlling raw material costs in companies where research is carried out in increasing the efficiency of procurement of raw materials and optimizing the use of resources.